Theatricalising Law in Three, 1929-1939 (Brisbane) - Marett Leiboff (Law Text Culture, 2016)
I begin this article with a manoeuvre that presages three stories of lives lived with law. But because they speak of law past, there is a temptation to read them as curiosities, when their purpose – the thing I ask of them – is to disorient and challenge, to prompt and trigger the questions: ‘what do I bring to law, what do I miss because I am me, and what do I see because I am me?’ So rather than an exercise in law past, my purpose is to use those stories of law past to trigger something in us, as legal interpreters, now, as an ‘exercise in revolt … against oneself ’. I want the stories to challenge our own lives by asking – ‘what could I know in law through the life of someone in law other than me’.